Description Of Implementation Of Ventilator Bundle (VB) at ICU Of Mangusada District Hospital - I Nyoman Asdiwinata; Sukra Andini Ni Komang; Yustin Arvanita Dewa Ayu (Health and Technology Journal (HTechJ), 2023)
The ventilator is a breathing apparatus that maintains oxygen delivery for a long time. One of the impacts caused by using a ventilator for a long time is a nosocomial infection called Ventilator Associated Pneumonia (VAP). Research is a quantitative descriptive study using a cross-sectional research design. The population in this study amounted to 30 with a non-probability type sample, and researchers will use a total sampling technique. There were 17 women (56.7%) who had washed their hands, in the ICU training characteristics, there were 14 people (46.7%) who did not have ICU training who had done hand washing, and there were 15 people (50%) nurses with D3 nursing education who had done washing hands. There were 18 people (60%) of the female sex had taken oral hygiene measures. In the ICU training characteristics, there were 15 people (50%) who did not have ICU training who had carried out oral hygiene. In the characteristics of the education level, 17 people (56.7%) with an education level of D3 nursing have already performed oral hygiene. VAP Bundles are a set of evidence-based practices (EBP) that result in VAP improvements when carried out collectively and consistently by health workers, namely nurses and doctors responsible for patients on mechanical ventilators.